Improved enzymatic procedure for the synthesis of anandamide and N-fatty acylalkanolamine analogues: A combination strategy to antitumor activity - Quintana, Paula Gabriela; Garcia Liñares, Guadalupe Eugenia; Chanquia, Santiago Nahuel; Gorojod, Roxana Mayra; Kotler, Monica Lidia; Baldessari, Alicia (European Journal of Organic Chemistry)
Twenty N-fatty acylamines from linolenic and arachidonic acids, fifteen of them new compounds, were obtained through Candida antarctica B lipase-catalyzed esterification and aminolysis reactions in very good yields and with high chemoselectivity. The optimal reaction conditions were achieved by studying the reaction parameters (temperature, E/S ratio, alcohol and alkanolamine/fatty acid ratio, time, solvent, free-solvent system, etc.). To identify ideal enzymatic methods for generating the alkanolamides we evaluated enzyme performance in three procedures: i) aminolysis of ethyl ester, ii) direct condensation between the fatty acid and the alkanolamine, and iii) a one-pot/two-step conversion of fatty acids into alkanolamides via in situ formation of the ethyl ester and subsequent aminolysis by the alkanolamine. The advantages noted with the enzymatic methodology, such as mild reaction conditions and low environmental impact, underscore biocatalysis as a convenient way to prepare the reported compounds. The cytotoxic activities of all compounds and mixtures of anandamide and its analogues were evaluated in rat glioma C6 cells. These studies reveal that some anandamide analogues enhance the antitumor effects of anandamide, suggesting their possible application as therapeutic tools in cancer treatment. Twenty N-fatty acylamines from linolenic and arachidonic acids were obtained by one-pot/two-step Candida antarctica B lipase-catalyzed esterification and aminolysis reactions in very good yields with high chemoselectivity. Cytotoxicity assays using rat glioma C6 cells revealed that some analogues enhanced the antitumor effects of anandamide (AEA), suggesting possible anticancer applications. Fil: Quintana, Paula Gabriela. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Unidad de Microanálisis y Métodos Físicos en Química Orgánica. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Unidad de Microanálisis y Métodos Físicos en ...